1996
DOI: 10.1023/a:1016023111248
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Formulations of MA-SME were shown to generate substantial enhancement (up to 12-fold) of the rat oral bioavailability of DDAVP with regard to simple saline solution of the drug. From the results it is also evident that MA-SME, but not plain-SME or non-SME Carbopol solution, is responsible for the enhancement of oral delivery of DDAVP in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The results observed were an extensive and persistent fall in plasma calcium level after oral administration of the mucoadhesive emulsion, indicating the absorption of EC from the emulsions adhered to the mucosa, as suggested by many researchers. 4,5,9,26) In the experiment using the emulsions containing FD-4, in fact, a strong mucoadhesion of mucoadhesive emulsion to the mucosa was demonstrated (Table 3). Thus, the usefulness of mucoadhesive emulsions for the oral administration of EC was demonstrated.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results observed were an extensive and persistent fall in plasma calcium level after oral administration of the mucoadhesive emulsion, indicating the absorption of EC from the emulsions adhered to the mucosa, as suggested by many researchers. 4,5,9,26) In the experiment using the emulsions containing FD-4, in fact, a strong mucoadhesion of mucoadhesive emulsion to the mucosa was demonstrated (Table 3). Thus, the usefulness of mucoadhesive emulsions for the oral administration of EC was demonstrated.…”
Section: Discussionmentioning
confidence: 95%
“…Considerable attempts have been made to develop an efficient drug delivery system for the oral administration of these peptides. Trials for the oral route have used mucoadhesive nanoparticles, 4,5) W/O/W multiple emulsions, 10,21,25) mucoadhesive submicron emulsions 9,26) and surface-coated liposomes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the oral absorption of vitamin A, vitamin D 3 and insulin was improved by administering them as milk fat globule membrane emulsions [7]. Improved oral delivery of cefpodoxime proxetil [8] and desmopressin [9] from submicron emulsions has been reported. Relatively higher oral availability of drugs contained in cationic emulsions was also reported [10].…”
Section: Myers and Stellamentioning
confidence: 99%
“…Based on the promising potential and good acceptance of orally administered drug delivery systems, some recent research has examined alternative application methods for desmopressin to enhance BA. By using a mucoadhesive submicron emulsion, a 12-fold increase in the BA of DDAVP was observed compared with a pure saline solution ( Ilan et al, 1996 ). The incorporation of DDAVP into mucoadhesive, multi-layer film preparations has also been investigated ( Lindert, 2016 ).…”
Section: Introductionmentioning
confidence: 99%